Synthesis of Co/SiO2 nanosize particles by a reverse micelle and sol-gel processing - Bae, DS; Kim, DJ; Han, KS; Adair, JH (KOREAN ASSOC CRYSTAL GROWTH, INC, 2002)
CO/SiO2 composite particles have been synthesized with in reverse micelle via metal alkoxide hydrolysis and condensation. The size of the particles and the thickness of the coating cart be controlled by manipulating the relative rates of the hydrolysis and condensation reactions of tetraethoxysilane (TEOS) within the micro-emulsion. The average size of synthesized particles was about in the size range 20-40 mm. The effects of synthesis parameters, such as the concentration of Co solution, the molar ratio of water to TEOS, and the molar ratio of water to surfactant, are discussed.
Keywords: QUANTUM SIZE; SEMICONDUCTOR